Biomechanical effects following footstrike pattern modification using wearable sensors - Chan, P. P. K.; Chan, Z. Y. S.; Au, I. P. H.; Lam, B. M. F.; Lam, W. K.; Cheung, R. T. H. (Journal of Science and Medicine in Sport, 2021)
This study sought to examine the biomechanical effects of an in-field sensor-based gait retraining program targeting footstrike pattern modification during level running, uphill running and downhill running. Design: Quasi-experimental design. Methods: Sixteen habitual rearfoot strikers were recruited. All participants underwent a baseline evaluation on an instrumented treadmill at their preferred running speeds on three slope settings. Participants were then instructed to modify their footstrike pattern from rearfoot to non-rearfoot strike with real-time audio biofeedback in an 8-session in-field gait retraining program. A reassessment was conducted to evaluate the post-training biomechanical effects. Footstrike pattern, footstrike angle, vertical instantaneous loading rate (VILR), stride length, cadence, and knee flexion angle at initial contact were measured and compared. Results: No significant interaction was found between training and slope conditions for all tested variables. Significant main effects were observed for gait retraining ( p-values = 0.02) and slopes ( p-values = 0.01). After gait retraining, 75% of the participants modified their footstrike pattern during level running, but effects of footstrike pattern modification were inconsistent between slopes. During level running, participants exhibited a smaller footstrike angle ( p = 0.01), reduced VILR ( p = 0.01) and a larger knee flexion angle ( p = 0.01). Similar effects were found during uphill running, together with a shorter stride length ( p = 0.01) and an increased cadence ( p = 0.01). However, during downhill running, no significant change in VILR was found ( p = 0.16), despite differences found in other biomechanical measurements ( p-values = 0.02-0.05). Conclusion: An 8-session in-field gait retraining program was effective in modifying footstrike pattern among runners, but discrepancies in VILR, stride length and cadence were found between slope conditions.